Analysis Of Aedes Aegypti Larvae Population Density, Kasturian Village, South Ternate, Ternate City, Indonesia - Tomia, Amalan; Tomia, Sumiati (Publisher Cv. Inara, 2025)
Introduction. This study aims to determine the level of population density of Aedes aegypti mosquito larvae as an effort to control dengue fever in Kasturian Village. Ternate City. Method. The sample of this study was larvae taken from 100 houses in Kasturian Village, North Ternate District, Ternate City that have containers both inside and outside the house. The data obtained were analyzed for larval index using the House Index (HI), Container Index (CI), and Breteau Index (BI) formulas. The relationship between habitat characteristics and population density of Aedes sp mosquito larvae was analyzed using the SPSS program.Results And Discussion . The survey results found that the characteristics of the Ae. aegypti mosquito larvae habitat consisted (TPA )container types including bathtubs, toilet tubs, drums, jugs, ablution water, cergen and buckets, and non containers including used cans (non0TPA), used tires, used glasses or bottles, flower vases, aquariums, dispenser containers, washbasins, gutters, and used drums. The type of container that is predominantly positive for larvae is the TPA container type, dark in color, found in the house and does not use a cover. The results of the analysis of the density index of Ae. aegypti mosquito larvae are in the moderate category for CI and BI, while HI is in the high category. Conclusion. This can be explained that Kasturian Village has the potential for dengue virus infection (DBD) which needs to be watched out for